Business intelligence standardization and corporate strategy : a paradox - Jacquinet, Marc (2016)
Market evidence suggests the increased investment of companies in BI systems to feed their strategy processes. The change in the strategy fundamentals increases substantially the value of information for both strategies’ implementation and control. One domain neglected is the use of BI systems for strategy conception. And this is something increasingly important in today’s constantly changing world of business, where new information in a knowledge economy is usually synonymous of more added value and competitiveness. However, together with this tendency, we experience a general trend for BI systems standardization, a dominant movement for BI solutions providers to standardize processes in order to take advantage of learning curves and processes, and economies of scale and scope. Considering that each strategy should be unique, and departing from the principle that BI systems are closely related with corporate strategy, it seems that there is a double paradox in BI markets that companies should solve as soon as possible, in order to take the most out of the momentum of BI markets.